SYSTEM OF STABILIZATION OF REACTIVE MAGNETRON SPUTTERING PROCESS - A. P. Burmakou; V. N. Kuleshov; A. V. Stoliarov (Приборы и методы измерений, 2018)
Film coatings today allow to create large number of diverse structures in electronics, microelectronics, optics, architecture and construction. Leading technologies in this area are magnetron deposition technologies. The problem of magnetron deposition methods is insufficient reproducibility of the composition and properties of coatings, caused by the instability of the parameters of a magnetron discharge in the presence of a reactive gas. There are stabilization systems that make it possible to make reproducible films, but all of them have a number of issues. The aim of the work was to develop a system for stabilizing the reactive magnetron sputtering process for film coating technologies that will eliminate the described shortcomings of existing systems.The developed system of stabilization: automatic and cumulative of sensors, actuators, microcomputer with control software, as well as devices providing interaction of sensors and actuators with a microcomputer. The sensors of the system may be vacuum gauges or pressure sensors, discharge current and voltage sensors of sprays, optical sensors for recording spectral element processes, absorption of a plasma of a magnetron discharge. The actuators of the system are gas flowers, as well as valves. Number and type of sensors and actuators from existing technologies and requirements for ongoing processes. The control software allows to flexibly adjust the system (to form control loops, then to assign sensors and actuators in accordance and to choose control algorithms, to set parameters and operating modes of control loops). Thus, the developed system is adaptable to a wide range of process plants and processes.System operability was confirmed by the process of magnetron deposition of a titanium oxide film. The deviation of the level of the sensor signals from the required values during the process did not exceed 3 %, which allows obtaining high-quality coatings.